Dechorionated zebrafish embryos improve evaluation of nanotoxicity - Kim, Rosa; Heo, Yunwi; Yoon, Hakwon; Park, June-Woo (Frontiers in Toxicology, 2024)
IntroductionIn response to the growing need to evaluate nanomaterial (NM) toxicity and compliance with the “3Rs” principles (replacement, reduction, and refinement of animal experiments), zebrafish (Danio rerio) embryos have emerged as a promising alternative model for studies on NM toxicity. However, zebrafish embryos are surrounded by an acellular envelope, the chorion, which limits the permeability of NMs. The present study investigated the importance of dechorionated zebrafish embryos for evaluating NM toxicity.MethodsWe utilized confocal microscopy and field-emission scanning electron microscopy with energy-dispersive spectroscopy to observe the permeability of NMs into the embryonic body using 50-nm fluorescein 5 (6)-isothiocyanate-incorporated silica nanoparticles (FITC-SiO2NPs). We investigated the physiological effects of removing the chorion using pronase on zebrafish embryos. Nanotoxicity was compared depending on the presence or absence of the chorion in zebrafish embryos using the standardized method ISO/TS 22082:2020.ResultsThe FITC-SiO2NPs were adsorbed onto the embryonic chorion; the Si content was higher in the chorion than in the embryonic body and higher in the intact zebrafish embryos than in the dechorionated ones. Dechorionated zebrafish embryos exhibited no negative physiological effects. The LC50 values of several NMs were lower in dechorionated embryos than those in intact ones.ConclusionDechorionated zebrafish embryos exhibited greater sensitivity to NMs than usual. To the best of our knowledge, this is the first study to evaluate NM toxicity using a new standardized test method, ISO/TS 22082:2020, and could contribute towards the increased utility of dechorionated embryos as an alternative model for the evaluation of nanotoxicity.